Track Vibration Based Signal System for Unattended Rail Crossing and on Track Signalling - Ameen, Mohamed (International Journal of Computer Sciences and Engineering, 2025)
Number of unattended level crossing accidents and people involved in train track accidents are increasing after each year as per the rail accidents statistics in previous year . Most cases involve accidents due to the carelessness, sound of train not heard and accidents on curved tracks as train suddenly appear .Possibility of providing manned level crossing at regular intervals of distance is merely possible as lot of infrastructure , human resource and track modification are to be performed . The fatalities can be minimized to a great extend if a vision based signal system can be implemented , which could provide a signal when the train is about to pass and signal stays on until all the compartment pass. As the sense of vision provides much more attention than any other sense. The system can be implemented easily and left unattended with minimal maintenance also the system can be positioned at regular intervals of track with less track modification.